Bacteriophage Treatment of Infected Diabetic Foot Ulcers - Morozova, Vera V; Kozlova, Yulia N; Ganichev, Denis A; Tikunova, Nina V (Methods in molecular biology (Clifton, N.J.), 2018)
Diabetic foot ulcers occur as a common complication of diabetes. Healing of the ulcers is largely delayed by the concomitant infection. Antibiotic treatment of infected ulcers is complicated by formation of microbial biofilms , which are often heterogeneous and resistant to antibiotics. Bacteriophage therapy is considered as an additional approach to the treatment of infected wounds. Here, we describe the basic method of application of bacteriophages for treatment of infected diabetic foot ulcers, including ones that are very large.